Museu Parque Seringal, Ananindeua, Pará: um patrimônio, múltiplas possibilidades - SILVA, Ana Daniela Nogueira da (2019)
This study aims to reflect on the institutionalization of the Museu Parque Seringal (MUPS), located in the city of Ananindeua, in the surroundings of Belém, Amazonian Pará state, and its reflections on the relationships established between the local community and the local heritage. The MUPS was the focus of public environmental protection policies aimed at the preservation of the rubber trees (Hevea brasiliensis) considered as natural and cultural patrimony of the city. The methodology included the bibliographical survey regarding the categories museum, park and heritage, in order to reflect on the association between them; historical research of the local and configuration; survey of the documents related to the foundation of the institution available in the websites of the Ananindeua city; fieldwork to observe the daily life at the institution and in the community in order to understand the existing relationships. The techniques used were recorded interviews and questionnaires that allowed me to gather information for analysis that support the reflections. The results reveal that MUPS is considered by the employees and the community as an environmental park associated to a museum. The relationships between the community and the institution are taken towards the natural aspect of the heritage, and the Museum maintains only one permanent exhibition whose activity is affected due to the lack of structural management of the museum, which leads to the weaken of MUPS’s museological aspect. This problem is probably related to the sparse reflections about the concept of museum, which can be solved by implementing the necessary museological practices so that MUPS can act with the community.